Autistic Self-Advocacy and the Neurodiversity Movement: Implications for Autism Early Intervention Research and Practice - Leadbitter, Kathy; Buckle, Karen Leneh; Ellis, Ceri; Dekker, Martijn (Frontiers in Psychology, 2021)
Over the past two decades, the growth of autistic self-advocacy and the neurodiversity movement has brought about new ethical, theoretical and ideological debates within the world of autism theory, research and practice. These debates and discussions have had genuine impact within some areas of autism research but their influence is less evident within early intervention research. In this paper, we argue that all autism intervention stakeholders need to understand and actively engage with the views of autistic people and with neurodiversity as a concept and movement. In so doing, intervention researchers and practitioners are required to move away from a normative agenda and pay diligence to environmental goodness-of-fit, autistic developmental trajectories, internal drivers and experiences, and autistic prioritised intervention targets. We focus on psychosocial intervention programmes for young autistic children and reflect upon the purpose of early autism intervention, the types of intervention methods we use, and how these align with the priorities of autistic people. We then reflect upon issues pertinent to research into early autism intervention researchers must respond to these debates and the opportunities presented by reframing effectiveness, developing measurement tools to measure autistic prioritised outcomes, and forming partnerships with autistic people. We point to future directions. There is a pressing need for increased reflection and articulation around how intervention practices align with a neurodiversity framework and greater emphasis within intervention programmes on natural developmental processes, coping strategies, autonomy and wellbeing.